Perception of Medical Error Among Resident Doctors at the University College Hospital (Uch), Ibadan - Victoria, Tawose Oluwatomisin; Oluwabukola, Alawale; Oluwasegun, Ayinde Abayomi; Gbolahan, Abbas Olaniyi; Akinyode, Aknifemi (Journal of Medical Genetics and Clinical Biology, 2024)
To enhance the standard of patient care, it is necessary to look into the complex issue of resident doctors' perceptions of medical error at tertiary hospitals. To foster a culture of safety in medical practice, medical mistake must be addressed in Nigeria, where it is a major contributor to patient mortality and morbidity. Therefore, this study aimed to determine the perception of medical error among resident doctors in the University College Hospital, Ibadan. In order to choose a sample of 302 resident doctors from a pool of 515 at the University College Hospital (UCH), a two-stage sampling approach was used. The research methodology used in this study was a cross-sectional survey employing a pretested self-administered semi-structured questionnaire. At the 0.05 level of significance, data were analyzed using descriptive statistics as well as inferential statistics like chi-square 228 (75.5%) of the responders were men, and 74 (24.5%) were women. Approximately 33.4% of the respondents were pre-part 1, 64.9% of resident doctors were post-part 1, and 1.7% were post-part 2 of their fellowship tests. The majority of responders (82.1%) had between one and three years of resident doctor experience. A majority (70.2%) of the respondents reported that misdiagnosis generally often occur in a medical setting. About 40.4% of the respondents said that delayed diagnosis is the most common type of medical error in the institution. There was a statistical significant association between the frequency of occurrence of delayed diagnosis and the departments of the resident doctors (X²=16.892, P<0.001). A majority (62.3%) of respondents reported that high work load, ill-equipped facility, work environment, patient factor and institutional factors influence their daily medical practice. Most (88.1%) of the respondents believed prevention of medical error is very crucial in the healthcare system. About 31.5% of the respondents indicated that continuous education on preventing and managing medical error was not adequately provided for resident medical doctors. The institution needs to invest in better-equipped facilities that will support high-quality patient care, continue medical education to advance medical knowledge and skills related to medical error, deploy more medical personnel to lessen the burdensome workload on current staff members, and establish proactive error avoidance strategies for the management of medical malpractice. This will thus improve the quality of healthcare delivery and reinforce possible standards of care that are evidence-based against medical error.